2021
DOI: 10.1080/15548627.2021.1953847
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of autophagy by SARS-CoV-2 proteins

Abstract: As part of innate immune defenses, macroautophagy/autophagy targets viruses and viral components for lysosomal degradation and exposes pathogen-associated molecular patterns to facilitate recognition. However, viruses evolved sophisticated strategies to antagonize autophagy and even exploit it to promote their replication. In our recent study, we systematically analyzed the impact of individual SARS-CoV-2 proteins on autophagy. We showed that E, M, ORF3a, and ORF7a cause an accumulation of autophagosomes, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 1 publication
0
85
1
Order By: Relevance
“…Xenophagy can be activated as an innate immune response to degrade intracellular microbes when cells are being invaded [ 54 ]. With the persistent infection of pathogenic microbes, the virulence factors from pathogenic microbes can evolve into a variety of mechanisms to evade the elimination of autophagy via blocking autophagic flux, and the cellular components of autophagosome was degraded as nutrition and energy for their persistent growth and colonization [ 55 ]. Therefore, xenophagy is a highly dynamic and multifactor process during the pathogenic microbe invasion [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xenophagy can be activated as an innate immune response to degrade intracellular microbes when cells are being invaded [ 54 ]. With the persistent infection of pathogenic microbes, the virulence factors from pathogenic microbes can evolve into a variety of mechanisms to evade the elimination of autophagy via blocking autophagic flux, and the cellular components of autophagosome was degraded as nutrition and energy for their persistent growth and colonization [ 55 ]. Therefore, xenophagy is a highly dynamic and multifactor process during the pathogenic microbe invasion [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown the ability of the related SARS-CoV-1 ORF3a N terminal targeting antibodies, derived from convalescent patients' plasma, to induce the destruction of ORF3a-expressing cells by activation of the complement pathway [60]. In addition, Akerstrom et al (2006) have demonstrated that rabbit antisera specific for the N terminus of SARS-CoV-1 ORF3a (representing amino acids [15][16][17][18][19][20][21][22][23][24][25][26][27][28] resulting in a neutralising effect 48 h post infection in virus infected Vero E6 cells [61]. There was no corresponding neutralizing effect using antisera that recognized the C terminal region of SARS-CoV-1 ORF3a in two separate studies [61,62] after 2-4 days of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being the largest accessory protein of SARS-CoV-2 [5,6], ORF3a has received relatively little research attention, particularly during the pandemic, even though protein homologues were first discovered in SARS-CoV-1 nearly 20 years ago [7][8][9][10]. SARS-CoV-2 ORF3a, characterized as a viroporin [11], has been involved in various pathophysiological activities such as disturbance of cellular homeostasis [11], NLRP3 inflammasome activation [12,13], apoptosis induction [13,14] and disruption of autophagy [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…HOPS complex from interacting with the STX17 or RAB7, which prevented the fusion machinery packaging, leading to an abnormal autophagosome-lysosome fusion. Moreover, SARS-CoV-2-expressed ORF3a and ORF7a can directly induce lysosomes injury and impair their function, such as inhibiting their acidification (Hayn et al, 2021;Koepke et al, 2021;Miao et al, 2021;Shroff and Nazarko, 2021). By doing this, SARS-CoV-2 could escape host lysosome degradation.…”
Section: Viruses Counter Host Autophagy By Inhibiting the Autophagy Downstream Degradation Pathwaymentioning
confidence: 99%